Handheld or head-mounted? An experimental comparison of the potential of augmented reality for animal phobia treatment using smartphone and HoloLens 2 - De Witte, Nele A. J.; Buelens, Fien; Debard, Glen; Bonroy, Bert; Standaert, Wout; Tarnogol, Fernando; Van Daele, Tom (Frontiers in Virtual Reality, 2022)
Exposure therapy is an effective treatment for specific phobia that could be further enhanced through Augmented Reality (AR), a novel technology that can facilitate implementation of gradual exposure and promote treatment acceptability. Effective exposure interventions require stimuli evoking high levels of anxiety. Therefore, it is important to ascertain whether animals can induce anxiety in distinct AR modalities, such as Head-Mounted Displays (HMDs) and smartphones, which can differ in user experience and technological embodiment. This study compared the anxiety inducing potential and experienced realism of a spider within the HoloLens 2 AR headset and an AR smartphone application. Sixty-five participants were exposed to a virtual spider in a 5-step Behavioral Approach Task (BAT) through both the HoloLens 2 HMD and the PHOBOS AR smartphone application. Participants reported Subjective Units of Distress at each step and physiological arousal was measured using heart rate and Skin Conductance (SC). Results show that both technological modalities induced self-reported anxiety for spiders in a BAT task in a non-clinical sample. The Hololens 2 modality was also related to an SC increase. Perceived realism did not differ between modalities but was associated with increased anxiety in the HoloLens 2 modality. Findings demonstrate that both implemented modalities have potential for enabling Augmented Reality Exposure Therapy (ARET), although the role of experienced realism merits additional investigation. Future research should assess the effectiveness of ARET in clinical samples and assess whether new extended reality modalities, such as passthrough virtual reality, could accommodate observed limitations and improve ARET experiences and outcomes.